SARS-CoV-2 mutations acquired in mink reduce antibody-mediated neutralization - Hoffmann, Markus; Zhang, Lu; Krüger, Nadine; Graichen, Luise; Kleine-Weber, Hannah; Hofmann-Winkler, Heike; Kempf, Amy; Nessler, Stefan; Riggert, Joachim; Winkler, Martin Sebastian; Schulz, Sebastian; Jäck, Hans-Martin; et al. (Cell Reports, 2021)
Transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from humans to farmed mink has been observed in Europe and the US. In the infected animals, viral variants arose that harbored mutations in the spike (S) protein, the target of neutralizing antibodies, and these variants were transmitted back to humans. This raised concerns that mink might become a constant source of human infection with SARS-CoV-2 variants associated with an increased threat to human health and resulted in mass culling of mink. Here, we report that mutations frequently found in the S proteins of SARS-CoV-2 from mink are mostly compatible with efficient entry into human cells and its inhibition by soluble angiotensin-converting enzyme 2 (ACE2). In contrast, mutation Y453F reduces neutralization by an antibody with emergency use authorization for coronavirus disease 2019 (COVID-19) therapy and sera/plasma from COVID-19 patients. These results suggest that antibody responses induced upon infection or certain antibodies used for treatment might offer insufficient protection against SARS-CoV-2 variants from mink.
CRIS-Team Scopus Importer:2021-04-23
Keywords: antibodies; evasion; mink; mutation; neutralization; SARS-CoV-2; spike protein; variant; Y453F